Cambodia : Impact Assessment of Farmer Organizations on Food Security for Rural Poor - World Bank (Washington, DC, 2015)
This report assesses the impact of participation in farmer organizations (FOs) on food security of rural households in Cambodia. The study is particularly set out to following: (1) examine FOs’ roles and operation and challenges for improving household’s food security; (2) analyze household’s characteristics that determine participation in FOs; (3) assess the impact of FOs on food security and livelihood of the rural poor; and (4) provide specific recommendations for changes in relevant legal acts and regulatory frameworks associated with FOs. The study concentrates on three types of FOs based on their predominance in Cambodia. Farmer groups (FG) are informal gatherings with 10-30 members. Farmer associations (FA) have more than 30 members and can either be informal or formal if registered at the Ministry of Interior. Agricultural cooperatives (AC) are business oriented, registered at the provincial department of agriculture (PDA) and comprise generally more than 30 members. This report is structured as follows: section one gives introduction. Section two reviews international as well as Cambodia’s experiences in farmer organizations to promote rural livelihoods and agricultural development. Section three details the research methodology employed in this impact assessment. Section four presents the detailed empirical findings. Section five concludes the report with a summary of the policy implications and recommendations.